Serotonin synchronises convergent extension of ectoderm with morphogenetic gastrulation movements in Drosophila. - Colas, J.; Launay, J.; Vonesch, J.; Hickel, P.; Maroteaux, L. (Mechanisms of Development, 1999)
During Drosophila gastrulation, convergent extension of the ectoderm is required for germband extension. Adhesive heterogeneity within ectodermal cells has been proposed to trigger the intercalation of cells responsible for this movement. Segmentation genes would impose this heterogeneity by establishing a pair-rule pattern of cell adhesion properties. We previously reported that the serotonin receptor (5-ht(2Dro)) is expressed in the presumptive ectoderm with a pair-rule pattern. Here, we show that the peaks of 5-ht(2Dro) expression and serotonin synthesis coincide precisely with the onset of convergent extension of the ectoderm. Gastrulae genetically depleted of serotonin or the 5-ht(2Dro) receptor do not extend their germband properly, and the ectodermal movements becomes asynchronous with the morphogenetic movements in the endoderm and mesoderm. Associated with the beginning of this desynchronisation, is an altered subcellular localisation of adherens junctions within the ectoderm. Combined, these data highlight the role of the ectoderm in Drosophila gastrulation and support the notion that serotonin signalling through the 5-HT(2Dro) receptor triggers changes in cell adhesiveness that are necessary for cell intercalation.